Danske meningsdannere om køn og kulturel mangfoldighed - Pristed Nielsen, Helene (Politik, 2010)
Taking its theoretical starting point in the feminist criticism of Habermas ́ conception of the public sphere, the article illustrates on the basis of empirical material how 14 Danish opinion-makers talk about gender equality and cultural diversity. The statements by prominent members of Danish political parties, think tanks, social movements and editorial boards of national dailies are analysed in an intersectional perspective, which seeks to illuminate different conceptions of cross-cutting forms of diversity within Danish society. The conclusion is that gender equality is often voiced as both a Danish and a European value, whereas there are ambiguous statements about to what extent there is a connection between gender equality and perceptions of Islam as either a religion or a culture.